The Effect of Live Streaming Shopping, Online Customer View, and Affiliate Marketing on Impulse Buying through Customer Trust in E-Commerce TikTok Shop - Azhara, Cindy Ayu; Saputro, Edy Purwo (Institute of Computer Science (IOCS), 2025)
This study aims to use TikTok Shop customer trust as a mediator variable to study the effects of Live Streaming Shopping, Online Customer Reviews, and Affiliate Marketing on impulse buying. A closed-ended questionnaire survey of the data was created with a purposive sample of 151 students who had previously shopped through the TikTok Shop. The intensive method used here is based roughly on a Likert scale. The data obtained by the study were then processed using Structural Equation Modeling Partial Least Squares (SEM-PLS) techniques. Empirical results show that Live Streaming Shopping and Affiliate Marketing have a significantly greater effect on consumer behavior than online consumer reviews alone. Specifically, Affiliate Marketing has a significant and positive effect on Impulse Investment and Customer Trust, while Live Streaming Shopping significantly increases Customer Trust although its direct effect on Impulse Investment is not statistically significant. At the other end of the spectrum, online customer reviews showed only a very weak positive relationship with impulsive buying behavior and customer trust, implying their weak ability to incite impulsive purchasing tendencies. In addition, customer trust become a mediating variable and effectively bolster the link between live streaming shopping and affiliate marketing with impulse buying, while online customer reviews stay out of this mediation. This discovery affirms that live streaming and online customer review mechanisms must be developed as radio platforms for direct interactions between sellers buyers. It has been observed from reality that this kind of real-time interaction not only promotes trust but also speeds consumer acceptance of patterns and ushers in an energetic electronic shopping environment together